Prevalence and determinants of Tuberculosis among HIV infected patients in south Ethiopia - Fekadu, Sintayehu; Teshome, Wondu; Alemu, Getnet (The Journal of Infection in Developing Countries, 2015)
Introduction: Tuberculosis (TB) is a chronic infectious disease that has represented a major health problem over the centuries. The human immune deficiency virus (HIV)/AIDS has substantially altered the epidemiology of TB by increasing the risk of reactivating latent TB, increasing chance of TB infection once exposed to tubercle bacilli (re-infection) and by increasing the risk of rapid progression soon after infection. Methodology: This study employs a retrospective review analysis of patient medical records. A total of 499 HIV/AIDS patient cards were reviewed and variables were recorded. Frequencies and odds ratio were calculated to determine prevalence and associated risk factors respectively. Results: A total of 499 HIV/AIDS positive patient cards were reviewed. Ninety one (18.2%) of the study participants were found to have tuberculosis of which 20 (22%), 58 (64%) and 13 (14%) were smear positive, smear negative and extra-pulmonary tuberculosis cases, respectively. In multivariate logistic regression being female (AOR=0.39; 95% CI:0.20-0.77), WHO clinical stage 3 (AOR=5.66; 95%CI:1.79-17.94); WHO clinical stage 4 (AOR=7.89;95%CI:2.01-30.96); and functional status being ambulatory (AOR=2.22; 95%CI:1.06-4.64) were independently associated with tuberculosis-HIV co-infection with p value <0.05. Conclusion: Prevalence of tuberculosis was high. Among tuberculosis positive cases, the proportion of smear negative cases was also high which requires strengthening of TB diagnostic techniques. Tuberculosis was associated with some social demographic characteristics and clinical variables.